Mechanical Behavior of Polymeric Materials: Recent Study (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue is dedicated to the captivating and intricate field of polymer science and technology, particularly the myriad factors that shape the properties of polymer-based materials. In this context, it is crucial to equip our readers with a foundational understanding of what failure signifies in a polymer-based material. This understanding is not only a matter of academic interest but also a pressing need in the field of polymer science and engineering.Ultimately, the findings in the literature have made it clear that mechanical energy interacts with matter and materials in different ways in different environments and conditions. This, together with the correct analysis of material responses, will continue to be vital in the development of mathematical models to assist in material design optimization within a general framework of sustainability, with the end purpose of avoiding catastrophic failure situations such as structural collapses or material ruptures.The works compiled in this work offer excellent examples of the current and future trends in the field of the mechanical properties of polymeric materials. The eleven novel articles in this Special Issue provide information and inspiration for future approaches in this fascinating field of science.